Sex differences in cachexia outcomes and branched-chain amino acid metabolism following chemotherapy in aged mice - Stephen Mora; Gagandeep Mann; Olasunkanmi A. J. Adegoke (PLoS ONE, 2026)
Cachexia is a complex muscle wasting syndrome that affects the majority of hospitalized cancer patients receiving chemotherapy. It is often unresponsive to nutritional interventions, including provision of branched-chain amino acids (BCAAs: leucine, isoleucine and valine). BCAAs are anabolic for skeletal muscle. We wondered whether their ineffectiveness in managing cachexia might be related to altered metabolism of these amino acids, a subject that has received minimal attention. Because estrogen limits BCAA catabolism, we hypothesized that the effects of chemotherapy on cachexia in old mice would be worse in males compared to females, and that this would be related to greater tissue release of the BCAAs in males. To better reflect the age population for which cachexia is an issue, we treated aged male and female mice (18 ± 2 months) with the chemotherapy drug cocktail FOLFIRI (50 mg/kg 5-fluorouracil (5FU), 90 mg/kg Leucovorin, and 24 mg/kg CPT11) or vehicle twice per week for 6 weeks. This cocktail is used in treating colon cancer. Metabolism and concentrations of the BCAAs and their metabolites were measured in plasma and tissues. There was a main effect of chemotherapy, reflected in reduced body weight, skeletal muscle, myofibrillar protein content, anabolic signalling and protein synthesis. In response to chemotherapy, males showed worsened outcomes for skeletal muscle weight and ubiquitinated proteins; they also had higher total plasma BCAAs but reduced muscle BCAAs. There was a main effect of chemotherapy in reducing the expression of the BCAA transporter LAT1. In response to chemotherapy, gastrocnemius muscle of males but not females had reduced inhibitory phosphorylation of BCKD-E1α ser293 , corresponding with increased activity of this enzyme. Chemotherapy reduced muscle and liver ketoacids of the BCAAs only in females. These data suggest that sex differences in BCAA catabolism may be linked to the severity of chemotherapy-induced muscle damage and interventions against cachexia need to take this into account.